Analisis Efek Kualitas Layanan Dan Produk Terhadap Minat Beli Ulang Pelanggan E-Commerce - Puput Iswandyah Raysharie; Irawan Irawan; Lia Aulia Amanda Bakti; Lyvia Angelqica; Mutia Nisa; Nadia Salsabila Effendi; Rengga Andika Putra Herlambang; Selva Ayu Safitri; Yogi Agustin (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study looks at customer behavior on e-commerce platforms, with a particular emphasis on Shopee in Indonesia. The study involved 102 respondents to evaluate the relationship between variables. The results show that these factors have an impact on the repurchase intention of e-commerce customers on Shopee. The study was conducted using quantitative methods and used SPSS for statistical analysis. The results show that the components present in this study have an influence on customer repurchase intention. However, other factors not present in this study, for example, price, user experience, and promotion, may have a greater impact on customer repurchase intention than other factors. This study provides an in-depth understanding of the components that influence customers' willingness to make repeat purchases on e-commerce platforms. While product and service quality remain important, companies and marketers should consider these additional elements when they create their marketing strategies. This calls for further future research using large samples and deeper analysis to understand this more complex context and help run businesses better in the ever-evolving e-commerce market.